1993
DOI: 10.1111/j.1471-0528.1993.tb15241.x
|View full text |Cite
|
Sign up to set email alerts
|

Does elective cryopreservation of all embryos from women at risk of ovarian hyperstimulation syndrome reduce the incidence of the condition?

Abstract: Objectives To analyse the incidence and factors associated with the ovarian hyper‐stimulation syndrome (OHS) in our IVF/GIFT programme before and after the introduction of a strategy to cryopreserve all embryos from women judged to be at risk. Design Two hundred forty‐one consecutive IVF/GIFT cycles from January to December 1989. Setting Specialist fertility unit, Manchester, UK. Interventions Pituitary suppression was effected by a daily subcutaneous injection of buserelin (500 μg) beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 29 publications
0
35
0
4
Order By: Relevance
“…Wada et al reported that TEC in women with E 2 values >3500 pg/mL on the day of hCG administration did not decrease the overall incidence of the OHSS but decreased the incidence of severe OHSS compared with women who underwent fresh ET (23). Sixty percent of women with high E 2 levels in the cryopreservation group developed the syndrome, with 8% being severe.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Wada et al reported that TEC in women with E 2 values >3500 pg/mL on the day of hCG administration did not decrease the overall incidence of the OHSS but decreased the incidence of severe OHSS compared with women who underwent fresh ET (23). Sixty percent of women with high E 2 levels in the cryopreservation group developed the syndrome, with 8% being severe.…”
Section: Discussionmentioning
confidence: 92%
“…The mean number of collected oocytes was 25.5 AE 7.3 (range, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Fertilization was affected by ICSI.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes in this experimental group were compared with a group of historical controls with a similar estradiol concentration, but who had their embryos transferred to the uterus. In this study, 60 % of the historical controls with an estradiol > 3,500 pg/mL who had embryos transferred and became pregnant had OHSS, compared to 6 % of the women who had all their embryos cryopreserved [ 42 ]. Following a "freeze all" cycle, the patient is prepared for a cryopreserved embryo transfer in a subsequent cycle.…”
Section: Cryopreserving All Embryos and Delaying Embryo Transfer To Amentioning
confidence: 96%
“…This option is emotionally and financially taxing. The other option is embryo cryopreservation for embryo transfer (ET) in a nonstimulated cycle [7]. This technique is inconvenient and generally yields inferior pregnancy rates compared with fresh ET.…”
Section: Discussionmentioning
confidence: 99%